Nature of Forest Crime in Bangladesh: An Empirical Study on Modhupur Reserve Forest - Miah, Md. Abdul Kader; Mohiuddin, Anira; Chakrabarty, Srideb (Journal of Sustainability and Environmental Management, 2022)
The national sal forest, includes the Modhupur Reserve forest, which takes up 76% of the total space. Along with a variety of tree species, this forest is rich in biodiversity. This forest is also threatened by forest crime since it has attracted the attention of grabbers. The scope of forest crime in the Modhupur Reserve Forest was examined in this study. Other objectives include understanding the causes and consequences of forest crime on the ecosystem and humans, as well as the role of law enforcement in forest crime prevention. The study adopted a quantitative methodology and collected data using a non-probability purposive sampling technique. A total of 150 people between the ages of 18 and 83 were collected from the Modhupur Reserve Forest in Tangail. The study' main findings include the smuggling of Sal, Gujjar, and Acacia, deforestation and squatting on forestland, as well as the trafficking of endangered and rare animals and flora. The primary factors that substantially contribute to the growth of forest crime include corruption and dishonesty among forest employees, security personnel, authorities, and even locals. The presence of forest crime jeopardizes both human and natural equilibrium. Acute environmental problems and livestock survival have a significant association. Water scarcity, air pollution, and an increase in natural calamities are just a few of the severe environmental issues that Modhupur people are currently dealing with. Additionally, police involvement is insufficient to eliminate forest crime.